2019
DOI: 10.1111/joa.12955
|View full text |Cite
|
Sign up to set email alerts
|

Initial stages of development of the submandibular gland (human embryos at 5.5–8 weeks of development)

Abstract: The aim of this study was to determine the main stages of submandibular salivary gland development during the embryonic period in humans. In addition, we studied submandibular salivary gland development in rats on embryonic days 14-16 and expression in the submandibular salivary gland region with the monoclonal antibody HNK-1. Serial sections from 25 human embryos with a greatest length ranging from 10 to 31 mm (Carnegie stages 16-23; weeks 5.5-8 of development) and Wistar rats of embryonic days (E) 14-16 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…All these stages occurred prehatching except the last one occurred post-hatching. Similar results were observed in human 33,34 , in pig 35 , in rat 36 in quail 37 and in duck 38 . The pattern of the development of the lingual gland in birds is like that described for mammals but the terminal buds are formed at the same time as the lumen of the glands 38 .…”
Section: Discussionsupporting
confidence: 86%
“…All these stages occurred prehatching except the last one occurred post-hatching. Similar results were observed in human 33,34 , in pig 35 , in rat 36 in quail 37 and in duck 38 . The pattern of the development of the lingual gland in birds is like that described for mammals but the terminal buds are formed at the same time as the lumen of the glands 38 .…”
Section: Discussionsupporting
confidence: 86%
“…The first appearance of parasympathetic nerves in mouse SGs is during the initial bud stage at E12.5, as the PSG forms near the epithelial stalk of the budding gland (Knox et al 2010). It has been recently reported that the PSG in human embryos initiates at Carnegie stage 16 (CS16), with a robust PSG evident at CS17, when the submandibular gland has started to initiate (Quirós-Terrón et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These age groups represented the following developmental stages for tooth differentiation: the cap stage (9-13gw), the early bell stage (14-16gw), and the late bell stage (17-22gw) (Figure 1A–1E) (Nanci and TenCate, 2018; Nelson, 2020). We also collected submandibular salivary glands (SMSG) from three matched timepoints (12-13gw, 14-16gw, 17-19gw) that cover the pseudo-glandular and canalicular stages for salivary gland development (Quirós-Terrón et al, 2019) (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%